2016
DOI: 10.1002/app.44667
|View full text |Cite
|
Sign up to set email alerts
|

Tunable wettability and tensile strength of chitosan membranes using keratin microparticles as reinforcement

Abstract: Keratin particles with microscale are prepared by ball mill and its influences on the chitosan membrane is evaluated. Composite membranes with various content of keratin are fabricated, and their physical and chemical properties such as morphology, wettability, crystallization, thermal stability, tensile strength, and break elongation are investigated. Optical microscope and situ topographic scan mode of nano‐test system are used to examine the dispersion and aggregation of keratin on the surface of chitosan m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Figure 3d presents the mechanical properties of CS‐based films, revealing that the tensile strength and elongation at break increased with increasing SA content because of the concomitant increase in the extent of amidation and hydrogen bonding between the amino groups and hydroxyl groups of CS and the carboxyl and hydroxyl groups of SA. Thus, the resulting increase in molecular binding strength increased film tensile strength 61 . At the same time, SA addition changed the macromolecular chain structure of pure CS, and thus increased film flexibility 62 and elongation at break.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 3d presents the mechanical properties of CS‐based films, revealing that the tensile strength and elongation at break increased with increasing SA content because of the concomitant increase in the extent of amidation and hydrogen bonding between the amino groups and hydroxyl groups of CS and the carboxyl and hydroxyl groups of SA. Thus, the resulting increase in molecular binding strength increased film tensile strength 61 . At the same time, SA addition changed the macromolecular chain structure of pure CS, and thus increased film flexibility 62 and elongation at break.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the resulting increase in molecular binding strength increased film tensile strength. 61 At the same time, SA addition changed the macromolecular chain structure of pure CS, and thus increased film flexibility 62 and elongation at break. This mechanical property enhancement benefits the further application of CSbased films.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In addition, Ma et al applied chicken feather keratin (micro)particles, extracted using L-cysteine and ball milled after freeze drying, into chitosan to form composite membranes. They observed that the incorporation of keratin into chitosan decreased the contact angle from 98.18 to 58.28, while the tensile strength (6568 MPa) and elongation at break (15%) reach maximums at 6% keratin content, representing increases of 80% and 88%, respectively, when compared with the pristine chitosan membrane [282]. Similarly, Simchi et al prepared an injectable nanocomposite hydrogel by conjugating a copolymer (Pluronic F127, PEO 99 -PPO 65 -PEO 99 ) with chitosan and crosslinking with merino wool keratin.…”
Section: Chitosanmentioning
confidence: 99%
“…1646.9 cm -1 , 1544.7 cm -1 , 1403.9 cm -1 and 673.0 cm -1 were respectively VC=O stretching vibration of amide I band, VC-N stretching vibration and VN-H in-plane bending vibration of amide II band, VC-N stretching vibration f amide III band and absorption peak of amide IV band. The characteristic absorption peak of the amide band indicated that the extracted keratin had a classical polypeptide structure [18,19]. The VS-O stretching vibration absorption peak of cystine oxidation products appeared at 1051 cm -1 , which indicated that the disulfide bond of keratin was destroyed by alkali during hydrolysis [10].…”
Section: Resultsmentioning
confidence: 99%